2000
DOI: 10.1097/00007890-200004270-00014
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Liver Allograft Biopsies With Late Centrilobular Necrosis

Abstract: With regard to most liver allograft biopsies showing late CLN, it is possible to make a specific diagnosis despite overlapping histologic features; this allows specific therapy to be instituted. Ultimately this is likely to contribute to improved graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 22 publications
5
39
0
Order By: Relevance
“…All these findings support the concept that in the setting of CLN, lobular inflammation is a manifestation of AR. 1,10,[12][13][14] Our recent study also supports that notion by showing that lobular inflammation (when all the other etiologies have been excluded) is independently associated with AR in biopsies with CLN. 10 Cholestasis also has been recognized in association with CLN.…”
Section: Commentssupporting
confidence: 78%
See 2 more Smart Citations
“…All these findings support the concept that in the setting of CLN, lobular inflammation is a manifestation of AR. 1,10,[12][13][14] Our recent study also supports that notion by showing that lobular inflammation (when all the other etiologies have been excluded) is independently associated with AR in biopsies with CLN. 10 Cholestasis also has been recognized in association with CLN.…”
Section: Commentssupporting
confidence: 78%
“…10 Cholestasis also has been recognized in association with CLN. 2,10,14 Previous studies showed that the severity of cholestasis did not correlate with any other histopathologic findings, including those of AR. 12 However, a recent study showed that the presence of cholestasis in biopsies with CLN was the strongest independent predictor of the simultaneous presence of AR.…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…59,60 As in native livers, central perivenulitis in allografts has several causes (Fig. 2), including various forms of rejection (pure perivenular rejection and early chronic rejection), early autoimmune hepatitis, 72,74,97 compromised afferent or efferent blood flow, 73,87,98 and adverse drug reactions. Perivenular rejection can be missed clinically and In cases with no or minor portal inflammation, the differential diagnosis includes acute rejection, chronic rejection, and prediagnostic autoimmune hepatitis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…[11][12][13][14]16 However, central venulitis more frequently is associated with acute allograft rejection. It remains uncertain whether the majority of cases of central venulitis represent some form, including the refractory form of acute allograft rejection.…”
Section: Commentsmentioning
confidence: 99%